2007
DOI: 10.1002/bip.20828
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of paclitaxel conjugated with an ErbB2‐recognizing peptide, EC‐1

Abstract: The selective delivery of therapeutic agents to receptors overexpressed in cancer cells without harming the rest of the body is a major challenge in clinical oncology today. In this study, we report the design and synthesis of paclitaxel (PTX) conjugated with an erbB2-recognizing peptide (EC-1). The cyclic peptide EC-1 specifically binds to the extracellular domain of ErbB2 and selectively inhibits proliferation of breast cancer cells overexpressing ErbB2. PTX is a potent antitumor agent commonly used in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, ErbB2 has been used for targeting taxane to breast cancer. 27 Also, the taxanes can be conjugated with monoclonal antibodies (mAbs) against tumor cell surface markers. One example is cBR96doxorubicin, which is selectively internalized and activated by a wide variety of human carcinomas expressing an extended form of Lewis Y antigen [Le(y)].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ErbB2 has been used for targeting taxane to breast cancer. 27 Also, the taxanes can be conjugated with monoclonal antibodies (mAbs) against tumor cell surface markers. One example is cBR96doxorubicin, which is selectively internalized and activated by a wide variety of human carcinomas expressing an extended form of Lewis Y antigen [Le(y)].…”
Section: Discussionmentioning
confidence: 99%
“…ErbB2-recognizing peptide, EC-1, was conjugated with an anticancer drug, paclitaxel, to selectively inhibit the proliferation of breast cancer cells over-expressing ErbB2. 26 Loh et al 27 recently reported an approach using localizing peptide conjugates to transport small molecule inhibitors to the subcellular compartment of cells where a target enzyme can be found. Cathepsins are cysteine proteases that mostly exist in endolysosomal vesicles.…”
Section: Specific Delivery and Targetingmentioning
confidence: 99%
“…Daunomycin‐LTVSPWY conjugates were highly cytostatic and taken up efficiently by human cancer cells. ErbB2‐recognizing peptide, EC‐1, was conjugated with an anticancer drug, paclitaxel, to selectively inhibit the proliferation of breast cancer cells over‐expressing ErbB2 …”
Section: Specific Delivery and Targetingmentioning
confidence: 99%
“…Two copies of the cyclic peptide targeting receptor were conjugated to paclitaxel in the same manner as in the approach above and showed preferential cytotoxicity to integrin-expressing tumor cells. Several other prodrugs targeting somatostatin receptor [293], ErbB2 (receptor tyrosine kinases) [294], folate receptor [295], and luteinizing hormonereleasing hormone have been synthesized [296]. Receptors can be also targeted by monoclonal antibodies.…”
Section: Paclitaxel and Its Derivativesmentioning
confidence: 99%